MANAJEMEN PELAYANAN JEMAAH UMRAH DALAM MENINGKATKAN KEPUASAN JEMAAH PADA PT. ARRAFSYAH SAFARI HARAMAIN DI KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The main problem in this study is the management of the services of the Umrah congregation of PT. Arrafsyah Safari Haramain and supporting factors and inhibiting factors for congregation services. This research was conducted to know the Umrah Congregation Service Management PT. Arrafsyah Safari Haramain and supporting factors and inhibiting factors for congregation services. This type of research is descriptive qualitative with a service management approach the researcher uses this approach with several parties who are considered key informants who are used as appropriate informants to provide the answers needed by researchers related to the Umrah congregation service management PT. Arrafsyah Safari Haramain and supporting factors and inhibiting factors. The data collection method was carried out by observing, documenting, and interviewing the main director and staff of PT.Arrafsyah Safari Haramain. The data sources used are primary and secondary. Then data processing techniques and data analysis are carried out through three stages, namely data reduction data display, comparative analysis, and conclusion. The result of this study indicates that the Service Management of PT. Arrafsyah Safari Haramain provided good service. Evidenced by the response and comfort experienced by the pilgrims starting from departure, accommodation, consumption, and transportation in Saudi Arabia to returning to their homeland. However, even though it has proven its good service, PT. Arrafsyah Safari Haramain sometimes experiences a few problems, such as using his passport when he is in Jeddah. The supporting factors include adequate infrastructure and having professional supervisors and employees with complete operating permits. The inhibiting factor that disrupts the course of service activities to the congregation is the amount of competition that exists. The implications of this research in the implementation of services management are quite good by providing more intensive guidance and direction to create an impression and satisfaction for the congregation maintain harmonious relations and improve the quality of employees so that good cooperation is created.